Management of children’s acute diarrhea by community pharmacies in five towns of Ethiopia: simulated client case study - Abegaz TM; Belachew SA; Abebe TB; Gebresilassie BM; Teni FS; Woldie HG (Therapeutics and Clinical Risk Management, 2016)
Tadesse Melaku Abegaz,1 Sewunet Admasu Belachew,1 Tamrat Befekadu Abebe,1 Begashaw Melaku Gebresilassie,1 Fitsum Sebsibe Teni,2 Habtamu Gebremeskel Woldie3 1Department of Clinical Pharmacy, School of Pharmacy, Gondar University, Gondar, 2Department of Pharmaceutics and Social Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, 3Department of Hospital Pharmacy, Debremarkos Teaching and Referral Hospital, Debremarkos, Ethiopia Background: Acute diarrhea is the major cause of child morbidity and mortality in low-income nations. It is the second most common cause of death among children <5 years of age globally. The indispensable role of community pharmacists is clearly observed in the prevention and treatment of diarrhea. However, there is a paucity of data on how community pharmacies manage acute childhood diarrhea cases in Ethiopia. This study aimed to evaluate the experience of community pharmacies in the management of acute diarrhea in northern Ethiopia.Methods: A simulated case-based cross-sectional study was conducted in community pharmacies from five towns of northern Ethiopia between April 2015 and September 2015. Convenience sampling technique was used to select sample towns. A structured questionnaire was organized to collect the information. Descriptive statistics, chi-squared test, one-way analysis of variance, and binary logistic regression were performed to describe, infer, and test for association between the variables. SPSS for Windows Version 21 was used to enter and analyze the data. A 95% confidence interval and P-value of 0.05 were set to test the level of significance.Results: Approximately 113 community pharmacies were visited to collect the required data from five towns. Majority (78, 69%) of them were located away from hospitals and health care areas. Nine components of history taking were presented for dispensers. Regarding the patient history, “age” was frequently taken, (90.3%), whereas “chief complaint” was the least to be taken (23%), for patients presenting with diarrhea. Approximately 96 (85.0%) cases were provided with one or more medications. The remaining 17 (15%) cases did not receive any medication. A total of six pharmacologic groups of medications were given to alleviate acute diarrheal symptoms. Majority (66, 29.6%) of the medications were oral rehydration salts with zinc. The mean number of medications was 1.99 per visit. Components of advice, such as dose, frequency, duration, drug action, and adverse drug reactions, were found to vary among the five towns at a statistically significant level.Conclusion: Community pharmacies provided inadequate treatment for acute childhood diarrhea. Inappropriate history taking and incorrect drug and food instructions have been frequently encountered during acute diarrhea management. Practitioners working in northern Ethiopia should receive proper training on the management of acute childhood diarrhea. Keywords: acute diarrhea, children, community pharmacies, simulated case, northern Ethiopia